Nanodendritic gold/graphene-based biosensor for tri-mode miRNA sensing - Song, Yongchao; Xu, Tailin; Xu, Li-Ping; Zhang, Xueji (Chemical communications (Cambridge, England), 2019)
A nanodendritic gold/graphene-based biosensor that can perform fluorescence, SERS and electrochemical tri-modal miRNA detection in a single microdroplet has been developed. The biosensor was used to successfully perform tri-modal quantitative trace miRNA-375 detection, which enormously reduces false positive readings caused by interference and ambiguous signals, and has significant implications for use in precise physiological and pathological diagnosis.